Genghis Khan and the making of the modern world - Weatherford, Jack, 1946- (New York : Three rivers press, 2004)
A re-evaluation of Genghis Khan's rise to power examines the reforms the conqueror instituted throughout his empire and his uniting of East and West, which set the foundation for the nation-states and economic systems of the modern era
The Mongol dynasties -- Introduction: The missing conqueror -- The reign of terror on the steppe, 1162-1206. The blood cot ; Tale of three rivers ; War of the Khans -- The Mongol world war, 1211 -1261. Spitting on the golden Khan ; Sultan versus Khan ; The discovery and conquest of europe ; Warring queens -- The global awakening, 1262-1962. Khubilai Khan and the new Mongol empire ; Their golden light ; The empire of illusion -- Epilogue: The eternal spirit of Genghis Khan
Originally published in hardcover in 2004 by Crown Publishers; published in paperback in 2005 by Three Rivers Press
Includes bibliographical references (pages 293-300) and index
Keywords: Genghis Khan, -- 1162-1227; Mongols -- Kings and rulers -- Biography; Mongols -- History